32.2: 360‐degree Floating Light Field Three‐dimensional Display Based on a High‐frame‐rate Color Projector. Issue 1 (1st July 2013) - Xia, Xinxing; Wang, Han; Li, Haifeng; Peng, Yifan; Zheng, Zhenrong; Liu, Xu; Shen, Weidong
Abstract: With light field reconstruction technique, displaying a floating 3D image in the air is implemented. The high‐frame‐rate projector and rotating flat light field scanning screen are utilized to create the light field of real 3D scenes. The occlusion‐capable floating 3D image is presented just above the flat diffusing screen.